A Comparison of the Accuracy of Corporate and Security Analysts' Forecasts of Earnings: A Comment. - Steve Albrecht, William; Johnson, Orace; Lookabill, Larry L.; Watson, David J. H. (The Accounting Review, 1977)
Abstract Comments on an article about the accuracy of corporate and security analyst's forecast of earnings. Conditions for accurate forecasting; Criticisms on the article.